EFL Undergraduate Students’ Competence, Relatedness, and Autonomy in Online Learning: A Self-Determination Perspective - Dwi Bayu; Eko Saputra (Juliet, 2023)
Due to the pandemic of Covid-19, numerous educational institutions have attempted to shift their pedagogical instruction from face-to-face to online teaching and learning. A plethora of studies have been published on how online learning should be provided. However, there is a paucity of research on the psychological needs that online learning provides for language learners. To bridge that gap, this descriptive study aims to investigate the university students' perspectives on psychological needs, particularly regarding their competence, relatedness, and autonomy concerning self-determination theory. The quantitative research design study attempts to investigate students' autonomy, competence, and relatedness in online tertiary learning. Sixty people were asked to fill out a survey-based questionnaire that included questions about autonomy (5 items), competence (5 items), and relatedness (8 items). The study's findings reveal that online grammar sessions meet undergraduate students' basic physiological learning needs despite the lack of physical human interaction. Among those three aspects, students' sense of relatedness had the highest mean. It meant the undergraduate students had no feeling of isolation while attending online learning. This present study suggests that teachers should consider students' interests to improve autonomy, competence, and relatedness.